1994
DOI: 10.1002/mrd.1080380409
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of spermatozoa and zona pellucida properties by the soluble acrosome reaction‐inducing factor of the ovulated egg‐cumulus complex

Abstract: Three sources of hamster periovulatory fluids (+/- heat inactivation at 56 degrees C), with bovine serum albumin (BSA) as control, were tested for effects on penetration of three classes of eggs by hamster sperm precapacitated in BSA. These fluids were a soluble extract of cumulus oophorus fluid (COF) from the ovulated hamster egg-cumulus complex, serum, and follicular fluid. Egg types were ovulated, salt-stored (ovulated), and follicular. In both COF and serum, there were significant differences among egg typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…There is considerable interest in identifying molecules present at the site of in vivo fertilization that act as cofactors for penetration and fertilization, potentially acting as acrosome reaction-inducing factor(s) (ARIF; [13][14][15][16]). Previously, we reported that the ovulated hamster egg cumulus complex contained a soluble, non-albumin ARIF that stimulated hamster sperm acrosome reactions and enhanced penetration through the zona pellucida [13,16,17]. The egg penetration-enhancing substance for follicular oocytes appeared to be of oviductal origin and functioned partly to increase the ARIF and spermbinding activities of the zona pellucida [17].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…There is considerable interest in identifying molecules present at the site of in vivo fertilization that act as cofactors for penetration and fertilization, potentially acting as acrosome reaction-inducing factor(s) (ARIF; [13][14][15][16]). Previously, we reported that the ovulated hamster egg cumulus complex contained a soluble, non-albumin ARIF that stimulated hamster sperm acrosome reactions and enhanced penetration through the zona pellucida [13,16,17]. The egg penetration-enhancing substance for follicular oocytes appeared to be of oviductal origin and functioned partly to increase the ARIF and spermbinding activities of the zona pellucida [17].…”
Section: Introductionmentioning
confidence: 95%
“…Previously, we reported that the ovulated hamster egg cumulus complex contained a soluble, non-albumin ARIF that stimulated hamster sperm acrosome reactions and enhanced penetration through the zona pellucida [13,16,17]. The egg penetration-enhancing substance for follicular oocytes appeared to be of oviductal origin and functioned partly to increase the ARIF and spermbinding activities of the zona pellucida [17]. The objectives of the current study were to identify the oviductal component that enhances sperm penetration into follicular eggs and to determine whether or not its mechanism of action is to stimulate acrosome reactions in capacitated sperm.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the oviduct is seen as a biologically active, dynamic tissue synthesizing and releasing macromolecules into the lumen throughout the estrous or menstrual cycle. Recent studies suggest a variety of oviduct-gamete [Buhi et al, 1993;Boatman et al, 1994] and oviduct-embryo [Gandolfi, 1995] interactions which indicate some regulation of these events. In this review, discussion will focus on the biosynthetic activity of the oviduct, identification and characterization of secretory protein molecules and current literature on the oviductal microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…The mass of DAG generated after EGF stimulation exceeds that potentially arising via PtdIns (4,5) Fig. 3.…”
Section: Discussionmentioning
confidence: 97%
“…It is generally believed that zona pellucida (ZP), the acellular oocyte coat, is the inducer of acrosomal exocytosis [1], with one of its glycoproteins (ZP3 in the mouse) being responsible for its exocytosis-inducing activity [2]. However, recent work has suggested that a series of molecules present in the cumulus-oocyte complex or in the oviductal ampulla (the site of fertilization) could also induce exocytosis or may act as co-factors during the initiation or completion of this process [3][4][5].…”
Section: Introductionmentioning
confidence: 99%